Metadata and education - Forczek, Erzsébet (Teaching Mathematics and Computer Science, 2012)
This article is a (possible) conceptual educational model, which introduces data representation, information storage and retrieval possibilities on the Web in a way analogous to the levels of organization of metadata.The model uses the traditional library and information systems as a starting point, referring to the levels and types of information organization, and describes directions of its development. General acquaintance with the dominant organizational levels and types helps to understand the information organization on the internet, the coexistence of both structured and unstructured elements, the closedness and deficiencies of the content of information, and also helps to find possible ways of correcting these deficiencies. One of the main advantages of model-driven approaches is that they, by using the well-known classical systems, make tangible the development of physical and content data organization types and levels of organization of information for medical students that usually do not possess informatics knowledge.The conceptual model presented in details in the article can provide a basis for a general introduction to metadata and to develop curricula equally appropriate for traditional face to face classes, trainings and online courses.